Determinants of Trade Balance in West African Economic and Monetary Union (WAEMU): Evidence from heterogeneous panel analysis - Keho, Yaya (Taylor & Francis, 2021)
This study investigates the determinants of the trade balance in West African and Monetary Union (WAEMU) over the period 1975–2017. We employ the Mean Group (MG) estimator along with the grouped mean version of Dynamic OLS (DOLS) and Fully Modified OLS (FMOLS) to deal with both endogeneity and cross-country heterogeneity. The results reveal that the trade balance is negatively related to domestic and foreign income whereas real effective exchange rate depreciation improves the trade balance in the long-run. However, the results do not confirm the short-run worsening of trade balance suggested by the J-curve. In the short-run, the trade balance is sensitive only to foreign real income but not to domestic income and real exchange rate. The country-level estimates show heterogeneity in the response of the trade balance to real exchange rate, domestic and foreign income. Overall, the findings of this study suggest that policies aimed at improving the trade balance should focus on the domestic production of imported goods, rather than devaluation.
Cogent Economics & Finance, Volume 9
Keywords: Exchange rate; trade balance; panel cointegration; WAEMU; École Nationale Supérieure de Statistique et d'Economie Appliquée d'Abidjan (ENSEA); Social/Econ Science